Investigation of ospC Expression Variation among Borrelia burgdorferi Strains - Xiang, Xuwu; Yang, Youyun; Du, Jimei; Lin, Tianyu; Chen, Tong; Yang, X. Frank; Lou, Yongliang (Frontiers in Cellular and Infection Microbiology, 2017)
Outer surface protein (OspC) is the most studied major virulence factor of Borrelia burgdorferi, the causative agent of Lyme disease. The level of OspC varies dramatically among B. burgdorferi strains when cultured in vitro, but little is known about what causes such variation. It has been proposed that the difference in endogenous plasmid contents among strains contribute to variation in OspC phenotype, as B. burgdorferi contains more than 21 endogenous linear (lp) and circular plasmids (cp), and some of which are prone to be lost. In this study, we analyzed several clones isolated from B. burgdorferi strain 297, one of the most commonly used strains for studying ospC expression. By taking advantage of recently published plasmid sequence of strain 297, we developed a multiplex PCR method specifically for rapid plasmid profiling of B. burgdorferi strain 297. We found that some commonly used 297 clones that were thought having a complete plasmid profile, actually lacked some endogenous plasmids. Importantly, the result showed that the difference in plasmid profiles did not contribute to the ospC expression variation among the clones. Furthermore, we found that B. burgdorferi clones expressed different levels of BosR, which in turn led to different levels of RpoS and subsequently, resulted in OspC level variation among B. burgdorferi strains.